Pemanfaatan Situs Makam Raja Tanjungpura Ketapang sebagai Sumber Belajar Sejarah Bagi Peserta Didik di Kelas X SMA Negeri 1 Muara Pawan - Tia Rahayu Pebrianti; Ika Rahmatika Chalimi; Haris Firmansyah (Journal on Education, 2024)
The purpose of this research is to explore how the Tanjungpura Ketapang King's Tomb Site can be used as a source of history learning for class X students at SMA Negeri 1 Muara Pawan. Research using a qualitative descriptive method approach. Data was obtained through interviews with history teachers, class Data collection was carried out through observation, interviews and document analysis. Data analysis uses an interactive approach, including data reduction, data presentation, and drawing conclusions. Data validity is guaranteed through triangulation of sources and techniques. Research findings include: (1) Although the material about the Tanjungpura Ketapang King's Tomb Site has not been officially included in the Learning Implementation Plan (RPP), it has been applied in history learning by linking it with historical material about Islamic Kingdoms in Indonesia, (2) The site The Tomb of the King of Tanjungpura Ketapang is used as a learning resource by teachers because it provides a rich educational experience by involving students in making direct visits to the site. (3) Several obstacles faced in this research include limited time during the learning process, especially when visiting the site. The Tomb of the King of Tanjungpura, and problems from students because some of them were less responsive when participating in the learning process, especially visiting the site.